2006
DOI: 10.1111/j.1540-8159.2006.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Delay Optimization by Doppler‐Derived Left Ventricular dP/dt Improves 6‐Month Outcome of Resynchronized Patients

Abstract: Doppler-derived dP/dt for AV delay optimization determines better functional class and LVEF at 6 months follow-up relative to an empiric AV delay program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…21 One possibility is that systematic optimization of the programmed AV delay might improve overall outcomes. However, even though many trials have shown acute benefits of AV optimization, 3,4,6,13,22 only limited data exist to suggest that systematic AV interval optimization results in long-term improvement in clinical outcomes. 20,[23][24][25][26][27] On the other hand, AV optimization by echocardiography is time-consuming and costly, and it would be desirable to avoid the procedure or, at the very least, to replace it with a simpler yet equally effective technique.…”
Section: Discussionmentioning
confidence: 99%
“…21 One possibility is that systematic optimization of the programmed AV delay might improve overall outcomes. However, even though many trials have shown acute benefits of AV optimization, 3,4,6,13,22 only limited data exist to suggest that systematic AV interval optimization results in long-term improvement in clinical outcomes. 20,[23][24][25][26][27] On the other hand, AV optimization by echocardiography is time-consuming and costly, and it would be desirable to avoid the procedure or, at the very least, to replace it with a simpler yet equally effective technique.…”
Section: Discussionmentioning
confidence: 99%
“…Modern DDD pacemakers allow a wide range of programming of AVD and AVD-related algorithms [6]. Proper setting of AVD allows to achieve electromechanical synchrony of atrial and ventricular contractions and the individual setting of AVD in patients with atrio-ventricular block can have the beneficial effects not only on the contractile function of the heart; but also on long-term prognosis [7]. Too short AVD results in initiation of ventricular contraction during atrial systole and hence abbreviates atrial systole and results in underfilling of the ventricle [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from single centers have shown improvement in cardiac output by echo Doppler-guided AVD optimization [11][12][13]. Doppler parameters used for echoguided optimization include aortic VTI [14,15]; diastolic mitral flow pattern by Ritter's method [16]; iterative method [17]; diastolic filling time [13]; VTI of mitral inflow [18]; Dopplerderived dP/dt [7]; tissue Doppler imaging [11,12]; LV and right ventricular (RV) pre-ejection delays; and myocardial performance index [19].…”
Section: Discussionmentioning
confidence: 99%
“…In various preliminary studies, optimization of the AV delay has been demonstrated to significantly increase hemodynamic response, New York Heart Association (NYHA) class, LVEF and B-type natriuretic peptide level in the short-time follow-up [10][11][12][13][14]. In contrast, the recently published SmartDelay determined AV Optimization: A comparison to Other AV Delay Methods Used in Cardiac Resynchronization Therapy (SMART-AV) trial implied otherwise.…”
Section: Av Delay Optimization and Qrs Fusionmentioning
confidence: 99%